2004
DOI: 10.3146/pnut.31.1.0002
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Decomposition of Peanut Residues in Georgia

Abstract: Legumes typically mineralize rapidly and can contribute to nitrogen (N) requirements of succeeding crops, but limited information exists on the mineralizable N content of peanut (Arachis hypogaea L.) residue. The objective of this study was to determine net N mineralization from two types of peanut residue for two soil types. Aboveground peanut residue (cv. Georgia Green) was collected 1 d prior to digging (PRE) and immediately after peanut threshing (POST). Leaf and stem residues were mixed and analyzed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
8
16
0
Order By: Relevance
“…During the first two years, the N concentration following peanut residue was lower as compared to removed peanut residue, but was higher the last year of the study (data not shown). The lower N concentration observed following retained peanut residue indicates that the peanut residue could have immobilized N, which is supported by the incubation study conducted by Balkcom et al (2004) Total C 1216 (18) 1247 (16) 1007 (41) Total N 48 (2) 32 (5) 38 (1) Total P 3.0 (0.2) 4.6 (0.6) 4.9 (0.04) concentration was higher following the retention of peanut residue. Since the N concentration and C/N ratio are related due to the relatively constant C concentration of plant tissues, the interaction for C/N ratio between year and peanut residue was similar to that of N concentration.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…During the first two years, the N concentration following peanut residue was lower as compared to removed peanut residue, but was higher the last year of the study (data not shown). The lower N concentration observed following retained peanut residue indicates that the peanut residue could have immobilized N, which is supported by the incubation study conducted by Balkcom et al (2004) Total C 1216 (18) 1247 (16) 1007 (41) Total N 48 (2) 32 (5) 38 (1) Total P 3.0 (0.2) 4.6 (0.6) 4.9 (0.04) concentration was higher following the retention of peanut residue. Since the N concentration and C/N ratio are related due to the relatively constant C concentration of plant tissues, the interaction for C/N ratio between year and peanut residue was similar to that of N concentration.…”
Section: Resultssupporting
confidence: 60%
“…Researchers in the U.S. Corn Belt have found that alfalfa (Medicago sativa L.) and soybean [Glycine max ( L.) Merr. ], can decrease the fertilizer N requirements of a succeeding corn (Zea mays L.) crop (Bruulsema & Christie, 1987;Bundy et al, 1993;Morris et al, 1993). Although peanut is a legume that is widely grown in the southeastern USA, no previous research has examined the N contribution of peanut residues to a rye cover crop utilized in a conservation system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Carolina, Hunt et al (1998) reported a low potential of N contribution to the soil system, which was consistent with their observation of no cotton yield response following peanut. An incubation of two soils with and without two types of peanut residue also indicated no significant amounts of N were mineralized under laboratory conditions (Balkcom et al, 2004). In contrast, other incubation studies have indicated peanut residues mineralized N and increased mineralization of indigenous and fertilizerderived soil N (Smith and Sharpley, 1990;Constantinides and Fownes, 1994).…”
Section: Introductionmentioning
confidence: 97%